The world’s most venomous spider is a species complex: systematics of the Sydney funnel-web spider (Atracidae: Atrax robustus) - Stephanie F. Loria; Svea-Celina Frank; Nadine Dupérré; Helen M. Smith; Braxton Jones; Bruno A. Buzatto; Danilo Harms (BMC Ecology and Evolution)
Abstract The Sydney funnel-web spider Atrax robustus O. Pickard-Cambridge, 1877 is an iconic Australian species and considered among the most dangerously venomous spiders for humans. Originally described in 1877 from a single specimen collected in “New Holland”, this spider has a complex taxonomic history. The most recent morphological revision of funnel-web spiders (Atracidae) lists this species as both widespread and common in the Sydney Basin bioregion and beyond, roughly 250 km from the Newcastle area south to the Illawarra, and extending inland across the Blue Mountains. Morphological variability and venom diversity in this species appear to be unusually high, raising questions about species concepts and diversity in these spiders. In this study, we use a combination of molecular phylogenetics, divergence time analyses and morphology to establish the Sydney funnel-web spider as a complex of three species. The “real” Sydney funnel-web spider Atrax robustus is relatively widespread in the Sydney metropolitan region. A second species, Atrax montanus (Rainbow, 1914), which is revalidated here, overlaps but mainly occurs further south and west, and a third larger species, Atrax christenseni sp. nov., is found in a small area surrounding Newcastle to the north. The revised taxonomy for funnel-web spiders may have practical implications for antivenom production and biochemical studies on spider venoms. Although no human fatalities have occurred since the development of antivenom in the 1980s, antivenom for Sydney funnel-web spiders might be optimized by considering biological differentiation at the species level.